The Implementation of Mangrove Forest Rehabilitation in Urumb Village, Semangga District, Merauke Regency - Moteh, Obeth; Amir, Astaman; Sunarni, Sunarni (Fakultas Perikanan UCM, 2023)
In the Presidential Regulation of the Republic of Indonesia Number 73 of 2012 concerning the National Strategy for Mangrove Ecosystem Management, it is explained that the life support system and natural resources are of very high value, therefore efforts are needed to protect, preserve and use sustainably for the welfare of the community. The purpose of this study is to determine the implementation of the community in mangrove forest rehabilitation in Urumb village, Semangga District, Merauke Regency. The research was conducted from September to November 2022, in Urumb Village. The research method used was qualitative descriptive with Purpusive sampling technique by determining the number of samples using the Slovin formula with a tolerance degree of 10%, so that a sample of 92 respondents from 1020 populations was obtained. The data collected in this study are primary and secondary data. The data analysis used in the study used qualitative data analysis of the Miles and Huberman model. The implementation of mangrove rehabilitation in Urumb Village consists of four activities, namely; Enrichment of biological resources consisting of mangrove planting activities and mangrove habitat improvement. Habitat improvement carried out in Urumb village in habitat improvement activities is a ban on sand excavation. Protection of mangroves so that they grow and develop naturally and are environmentally friendly. Keywords: Implementation of Mangrove Rehabilitation; Urumb Village; Merauke